Intra-articular Lesions: Imaging and Surgical Correlation - Schmaranzer, Florian; Todorski, Inga Almut Senta; Lerch, Till Dominic; Schwab, Joseph; Cullmann-Bastian, Jennifer; Tannast, Moritz (Seminars in Musculoskeletal Radiology, 2017)
The past 2 decades have seen a substantial increase in hip joint preserving procedures, primarily secondary to not only hip dysplasia, but the recognition and description of femoroacetabular impingement (FAI), and its association with chondral lesions, as a potentially pre-arthritic condition. Morphological magnetic resonance imaging (MRI) plays an essential role in the preoperative assessment of osseous deformities and in particular of the resulting joint degeneration. An accurate descriptive report of chondrolabral lesions is warranted describing the tear pattern, size, localization, and extension of the lesions. This is important because different damage patterns and localization of the lesions may determine the surgical approach. The current imaging standard is direct magnetic resonance arthrography (MRA) with a small field of view, with acquisition of radial images in addition to the classic coronal, sagittal, and axial-oblique images. Early cartilage damage detected on direct MRA obtained with or without traction can predict long-term failure after FAI surgery.
Keywords: labrum; cartilage; MRI; hip; traction